Celeberrimae urbes - celebres praedicatores. O medialnym znaczeniu mnichów żebrzących w średniowiecznym mieście - Igielska, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2013)
Celeberrimae urbes – celebres praedicatores. Mendicant friars as a medium of the medieval city. This article deals with media studies and discusses a problem thoroughly examined by historians of the Medieval period concerning the expansion of mendicant orders and their ministry work in the flourishing European cities of the 13th century. The research perspective – which differs from a strictly historical and theological point of view – emphasizes the impact of mendicant orders on communication in the rapidly changing social conditions of the era. Therefore, it allows one to interpret confrontations with wandering heretical preachers in the 12th century not only as a religious conflict, but also a confrontation with a certain way of distributing ideas that contested the existing state of affairs. It also makes it possible to expose the enduring features of the media role of the preacher, which determined his popularity until the Reformation.